Production of immunoregulatory cytokines in clinically asymptomatic periapical lesions depends on the lesions size - Duka Miloš; Gazivoda Dragan; Marković Milan; Majstorović Ivana; Tatomirović Željka; Mihajlović Dušan; Čolić Miodrag (Vojnosanitetski Pregled, 2019)
Bacground/Aim. Development of periapical lesions (PLs) involves a complex cross-talk between pathogenic microorganisms from the root canal and host immune mechanisms. In these processes proinflammatory cytokines are involved in stimulation of inflammation and osteodestructive mechanisms, whereas anti-inflammatory cytokines, with the immunoregulatory functions, have the opposite effects. How this balance is controlled is still the subject of numerous studies. The aim of this study was to examine whether the local production of interleukin (IL)-10, IL-27 and transforming growth factor (TGF)-β in human asymptomatic PLs depends on the lesion size and how levels of these immunoregulatory cytokines correlate with the cellular composition of PLs. Methods. The study was conducted on 30 PLs which were collected at the Clinic for Stomatology of the Military Medical Academy, Belgrade, Serbia. The PLs were divided according to their size into small- and largesize lesions (n = 12 and n = 18, respectively). The inflammatory cells (PL-ICs) were isolated from PLs and cultivated for 24 hours in culture medium supplemented with phorbol myristate acetate and Ca2+ ionophore. Cytospins were processed for immunocytology by using monoclonal antibodies to cell subsets. The levels of cytokines in culture supernatants were determined by the ELISA method. Statistical analysis was performed using the Student t-test and the Spearman’s correlation test. The values of p < 0.05 were considered to be significant. Results. The levels of IL-10 and TGF-β were significantly higher in the PL-ICs cultures of large-size lesions than in small ones (p < 0.01 and p < 0.05, respectively). In contrast, the levels of IL-27 were higher in the cultures of small-size lesions than in small ones (p < 0.05). Although the total number of PL-ICs and the proportion of mononuclear phagocytes were higher in the large-size PLs (p < 0.01 and p < 0.05, respectively), their main composition was not significantly different between the groups. The proportions of B cells/plasma cells (CD19/CD38+ cells), CD8+ T cells and CD14+ cells were significantly higher in the large-size PLs (p < 0.005; p < 0.05; p < 0.05, respectively). In contrast, the proportion of total T cells (CD3+ cells) was higher in the small-size lesions (p < 0.05). No statistically significant correlation was found between the levels of these cytokines and the composition/ phenotype of PL-ICs. Conclusion. This study suggests that IL-10, IL-27 and TGF-β may play different roles in suppression of unwanted immune/inflammatory reactions in asymptomatic PLs, depending on the extension of pathological process as judged by the size of lesions. [Project of the Serbian Ministry of Education, Science and Technological Development, Grant no. OI 175102]